2017
DOI: 10.1161/circresaha.117.311045
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB2 Regulates Cardiac Fibrosis Through Modulating the Interaction of Stat3 and TGF-β/Smad3 Signaling

Abstract: This study uncovered a previously unrecognized profibrotic role of EphrinB2 in cardiac fibrosis, which is achieved through the interaction of Stat3 with TGF-β/Smad3 signaling, implying a promising therapeutic target in fibrotic diseases and heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 27 publications
5
59
2
Order By: Relevance
“…This reversal of the fibrotic response to radiotherapy is accompanied by a significant reduction in circulating IL17 in the PANC272 model, a proinflammatory cytokine shown to participate in fibrosis formation (58). Our findings are supported by a cardiac fibrosis model, where it was shown that EFNB2 activates Stat3 and TGFb/Smad3 signaling to induce cardiac fibrogenesis (40), and lung and skin fibrosis models, where soluble EFNB2 promotes fibroblast chemotaxis and activation (41).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This reversal of the fibrotic response to radiotherapy is accompanied by a significant reduction in circulating IL17 in the PANC272 model, a proinflammatory cytokine shown to participate in fibrosis formation (58). Our findings are supported by a cardiac fibrosis model, where it was shown that EFNB2 activates Stat3 and TGFb/Smad3 signaling to induce cardiac fibrogenesis (40), and lung and skin fibrosis models, where soluble EFNB2 promotes fibroblast chemotaxis and activation (41).…”
Section: Discussionsupporting
confidence: 68%
“…High levels of expression of collagens Col1a2, Col2a1, and Col4a1 have been shown to associate with lower overall survival in patients with PDAC (70). In a cardiac fibrosis model, it was shown that EFNB2 activates Stat3 and TGFb/ Smad3 signaling to induce cardiac fibrogenesis (40), and in lung and skin fibrosis models, it was shown that soluble EFNB2 promotes fibroblast chemotaxis and activation (41). EFNB2 is known to be a regulator of TGFb1 signaling, and it has been shown that mice injected with lentivirus EFNB2 shRNA produce less active TGFb1 than control plasmid-injected mice (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A shedding of ephrinB2 into the alveolar space has been shown to occur during myofibroblast activation and lung fibrosis . Additionally, ephrinB2 has been implicated in cardiac fibrosis and increased endothelial adhesion molecule expression . The increased ephrinB2 levels indicate an increased ephrinB2 shedding, which could happen not only in pulmonary but also in systemic vessels.…”
Section: Discussionmentioning
confidence: 99%